A Dosimetric Comparison of Breast Radiotherapy Techniques to Treat Locoregional Lymph Nodes Including the Internal Mammary Chain. Issue 6 (June 2018) - Ranger, A.; Dunlop, A.; Hutchinson, K.; Convery, H.; Maclennan, M.K.; Chantler, H.; Twyman, N.; Rose, C.; McQuaid, D.; Amos, R.A.; Griffin, C.; deSouza, N.M.; et al.
Abstract: Aims: Radiotherapy target volumes in early breast cancer treatment increasingly include the internal mammary chain (IMC). In order to maximise survival benefits of IMC radiotherapy, doses to the heart and lung should be minimised. This dosimetry study compared the ability of three-dimensional conformal radiotherapy, arc therapy and proton beam therapy (PBT) techniques with and without breath-hold to achieve target volume constraints while minimising dose to organs at risk (OARs). Materials and methods: In 14 patients' datasets, seven IMC radiotherapy techniques were compared: wide tangent (WT) three-dimensional conformal radiotherapy, volumetric-modulated arc therapy (VMAT) and PBT, each in voluntary deep inspiratory breath-hold (vDIBH) and free breathing (FB), and tomotherapy in FB only. Target volume coverage and OAR doses were measured for each technique. These were compared using a one-way ANOVA with all pairwise comparisons tested using Bonferroni's multiple comparisons test, with adjusted P -values ≤ 0.05 indicating statistical significance. Results: One hundred per cent of WT(vDIBH), 43% of WT(FB), 100% of VMAT(vDIBH), 86% of VMAT(FB), 100% of tomotherapy FB and 100% of PBT plans in vDIBH and FB passed all mandatory constraints. However, coverage of the IMC with 90% of the prescribed dose was significantly better than all other techniques using VMAT(vDIBH), PBT(vDIBH) and PBT(FB) (mean IMC coverage ± 1 standard deviation = 96.0% ± 4.3, 99.8% ± 0.3 and 99.0% ± 0.2, respectively). The mean heart dose was significantly reduced in vDIBH compared with FB for both the WT ( P  < 0.0001) and VMAT ( P  < 0.0001) techniques. There was no advantage in target volume coverage or OAR doses for PBT(vDIBH) compared with PBT(FB). Conclusions: Simple WT radiotherapy delivered in vDIBH achieves satisfactory coverage of the IMC while meeting heart and lung dose constraints. However, where higher isodose coverage is required, VMAT(vDIBH) is the optimal photon technique. The lowest OAR doses are achieved by PBT, in which the use of vDIBH does not improve dose statistics. Highlights: Heart-sparing IMC radiotherapy is possible using a simple wide tangent in breath-hold technique. VMAT in breath hold is proposed as the optimum photon technique for IMC radiotherapy requiring higher isodose coverage. Breath-hold does not improve organ at risk dose for proton beam therapy.